Pattern Recognition Applications and Methods : 8th International Conference, ICPRAM 2019, Prague, Czech Republic, February 19-21, 2019, Revised selected papers /: 8th International Conference, ICPRAM 2019, Prague, Czech Republic, February 19-21, 2019, Revised selected papers. ([2020]) - Unknown
No abstract available